Intelligent and Interactive Computing Proceedings of IIC 2018 - Piuri, Vincenzo; Balas, Valentina Emilia; Borah, Samarjeet; Syed Ahmad, Sharifah Sakinah; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the latest research on computational approaches to learning. It includes high-quality peer-reviewed papers from the "Intelligent and Interactive Computing Conference (IIC 2018)" organized by the Universiti Teknikal Malaysia, Melaka. It uses empirical studies, theoretical analysis, and comparisons with psychological phenomena to show how learning methods can be employed to solve important application problems. The book also describes ongoing research in various research labs, universities and institutions, which may lead to the development of marketable products.
A Proposed Framework: Enhanced Automated Duplication Algorithm for Flash Application -- Publication Model for Academic Talent Based On Apriori Technique -- Software Module Clustering based on the Fuzzy Adaptive Teaching Learning based Optimization Algorithm -- Dynamic Solution Probability Acceptance within the Flower Pollination Algorithm for t-way Test Suite Generation -- A Study on Gamification for Higher Education Students' Engagement Towards Education 4.0 -- An Investigation of Learner Characteristics that Use Massive Open Online Courses (MOOC) in Learning Second Language -- Improved Ozone Pollution Prediction using Extreme Learning Machine with Tribas Regularization Activation Function -- Cultural Metadata Enhancement by Using Community-driven Approach to Create Digital Holistic Culture Conservation System -- Tracking Coastal Change over Kuala Terengganu using Landsat -- A Design of Automated Surgical Illumination System -- Image Spam Detection on Instagram using Convolutional Neural Network -- A Review of Botnet Detection Approaches Based on DNS Traffic Analysis -- Face Recognition using Texture Features and Multi-Layer Perceptron -- Classification of Landsat 8 Satellite Data Using Unsupervised Methods.
Keywords: Computational intelligence; Artificial intelligence; Quantum computers; Computer simulation; Computational Intelligence; Artificial Intelligence; Quantum Computing; Computer Modelling